Structure of the added value chain as a factor of competitiveness of the sector - Amirbekuly, Y.; Rakhimbekova, A.E. (KSU Publ., 2018)
This article examines issues related to the assessment of the competitiveness of enterprises, in particular, the oil refining industry. The technique of the chain of value added, which assesses the prospects of their state and development, is considered. Also, the article describes the tasks of managing the value chain, the solution of which will lead to the achievement of the main objective of the enterprise, which will entail an increase in the investment attractiveness and competitiveness of the enterprise. The paper gives an example of an assessment of key segments of KazMunayGas business: extraction, transportation, processing, the structure of the value chain and its change in dynamics are also considered. The dependence of investment attractiveness and competitiveness on the value and composition of value added was established and confirmed, and the sequence of the procedure for analyzing the value added was refined and the indicators reflecting the current state and position of the enterprise in the market from the point of view of consumers and competitors were specified. This technique allows you to solve several tasks, in particular, clarifying the value of the assets of the corporation.
Қосылған құн тізбегінің құрылымы саланың бəсекеге қабілеттілік факторы ретінде
Структура цепочки добавленной стоимости как фактор конкурентоспособности сектора
Keywords: value chain; investment attractiveness; competitiveness of the enterprise; gross profit of the segment; an estimation of cost of firm; analysis of the structure of the value chain; proceeds from sales; cost price